The detection of gravitational waves - Blair, David G. (Cambridge University Press, 1991)
Gravitational radiation has not been positively detected. Over the past two decades an army of extremely sensitive detectors has been built up, so that today its detection appears inevitable. In the opening chapters of this 1991 book David Blair introduces the concepts of gravitational waves within the context of general relativity. The sources of gravitational radiation for which there is direct observational evidence and those of a more speculative nature are described. He then gives a general introduction to the methods of detection. In the subsequent chapters he has drawn together the leading scientists in the field to give a comprehensive practical and theoretical account of the physics and technology of gravitational wave detection. David Blair has extensive knowledge of the subject and has visited most of the gravitational radiation experiments over the world. He has compiled a book which will be of lasting value to specialists, both the postgraduates and researchers in the field
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Gravitational waves / Measurement / Instruments; Detektor; Gravitationswelle